Human melanomas and ovarian cancers overexpressing mechanical barrier molecule genes lack immune signatures and have increased patient mortality risk. (1st December 2016) - Salerno, Elise P.; Bedognetti, Davide; Mauldin, Ileana S.; Deacon, Donna H.; Shea, Sofia M.; Pinczewski, Joel; Obeid, Joseph M.; Coukos, George; Wang, Ena; Gajewski, Thomas F.; Marincola, Francesco M.; Slingluff, Craig L.
ABSTRACT: We have identified eight genes whose expression in human melanoma metastases and ovarian cancers is associated with a lack of Th1 immune signatures. They encode molecules with mechanical barrier function in the skin and other normal tissues and include filaggrin (FLG), tumor-associated calcium signal transducer 2 (TACSTD2), and six desmosomal proteins (DST, DSC3, DSP, PPL, PKP3, and JUP). This association has been validated in an independent series of 114 melanoma metastases. In these, DST expression alone is sufficient to identify melanomas without immune signatures, while FLG and the other six putative barrier molecules are overexpressed in a different subset of melanomas lacking immune signatures. Similar associations have been identified in a set of 186 ovarian cancers. RNA-seq data from 471 melanomas and 307 ovarian cancers in the TCGA database further support these findings and also reveal that overexpression of barrier molecules is strongly associated with early patient mortality for melanoma ( p = 0.0002) and for ovarian cancer ( p < 0.01). Interestingly, this association persists for FLG for melanoma ( p = 0.012) and ovarian cancer ( p = 0.006), whereas DST overexpression is negatively associated with CD8 + gene expression, but not with patient survival. Thus, overexpression of FLG or DST identifies two distinct patient populations with low immune cell infiltration in these cancers, but with different prognostic implications for each. These data raise the possibility that molecules with mechanical barrier function in skin and other tissues may be used by cancer cells to protect them from immune cell infiltration and immune-mediated destruction.